Disability Friendly Library as a Manifestation of Inclusive Education: an Analysis of the National Library of Indonesia - Faiqotul Hasanah; Fasril Romadhon; Ripaie Ripaie; Wilda Alfia Zakia Fadila; Rusdiana Navlia (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
A disability friendly library is one tangible manifestation of inclusive education implemented at the National Library of Indonesia. This study employed a descriptive qualitative approach, with data collected through literature review and documentation. The findings indicate that the National Library of Indonesia has provided various facilities and services that support accessibility for persons with disabilities, including ramps, elevators, guiding blocks, accessible restrooms, Braille collections, audiobooks, and assistive technologies. These facilities create equal opportunities for students and people with disabilities to access information, learn independently, and actively participate in library activities. National Library Regulation Number 3 of 2023 concerning Social Inclusion-Based Library Transformation further reinforces the National Library's role as a reference for other libraries in Indonesia. This role is realized through staff training, the development of inclusive service standards, and the creation of learning spaces that are responsive to the needs of vulnerable groups, including persons with disabilities and older adults